Guerrilla Marketing (Trinity Journal of Management, IT & Media (TJMITM), 2011)
Guerrilla Marketing is low budgeted than heavy  advertisement programmes but it provides better result  through (WOM) Word-of-Mouth which leads to viral  process of marketing. The main objective of Guerrilla  Marketing is to make marketing campaign creative &  attractive in such a way that people can't stop talking  about it and campaign's message will spread in the form  of chain reaction in target audience. This process  needed investment of time, money & efforts which leads  to attainment of augmented customer base & profit. The  expansion of guerrilla term is self-explanatory for the  understanding of guerrilla marketing concept.
Keywords: Guerrilla; Buzz; A/DAS; Gimmick; Astroturf; flogs; (WOM) Word of mouth; Flyers